The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acssuschemeng.0c00420
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Conductivity of Bioinspired Nanofibrillated Cellulose Hybrid Films Based on Graphene Sheets and Nanodiamonds

Abstract: Polymer materials with high thermal conductivities play an important role in the development of next-generation electronics. In this work, high thermally conductive nanofibrillated cellulose (NFC) hybrid films based on nanodiamonds (NDs) and graphene sheets (GSs) were prepared by a facile vacuum-filtration self-assembly process. Inspired by the structure of nacre, zero-dimensional NDs, two-dimensional GSs, and one-dimensional NFC were used to build hierarchical structures, which lead to excellent mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…24 Based on these findings, some researchers indicated that incorporating the fillers with different sizes into the matrix was one of the effective ways to simultaneously take advantage of large and small fillers, because small fillers would fill in the gaps between large fillers, which was conducive to forming thermal conductive networks. [25][26][27][28][29][30][31][32][33][34] For example, Bian et al 25 fabricated epoxy resin composites with dopamine modified micro-BN and KH550 modified nano-Al 2 O 3 , and found that the composite possessed a TC of 1.182 WÁm −1 ÁK −1 , when the contents of BN and Al 2 O 3 reached 22.5 and 7.5 wt%, respectively. Guo et al 27 anchored Ag nanoparticles onto reduced graphene oxide (rGO) and fabricated Ag/rGOpolyamide (PI) composites, and reported that the composite's TC was 2.12 WÁm −1 ÁK −1 (Ag/rGO content:15 wt %), which was higher than that of rGO-PI composites at the same filler's content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Based on these findings, some researchers indicated that incorporating the fillers with different sizes into the matrix was one of the effective ways to simultaneously take advantage of large and small fillers, because small fillers would fill in the gaps between large fillers, which was conducive to forming thermal conductive networks. [25][26][27][28][29][30][31][32][33][34] For example, Bian et al 25 fabricated epoxy resin composites with dopamine modified micro-BN and KH550 modified nano-Al 2 O 3 , and found that the composite possessed a TC of 1.182 WÁm −1 ÁK −1 , when the contents of BN and Al 2 O 3 reached 22.5 and 7.5 wt%, respectively. Guo et al 27 anchored Ag nanoparticles onto reduced graphene oxide (rGO) and fabricated Ag/rGOpolyamide (PI) composites, and reported that the composite's TC was 2.12 WÁm −1 ÁK −1 (Ag/rGO content:15 wt %), which was higher than that of rGO-PI composites at the same filler's content.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, some researchers indicated that incorporating the fillers with different sizes into the matrix was one of the effective ways to simultaneously take advantage of large and small fillers, because small fillers would fill in the gaps between large fillers, which was conducive to forming thermal conductive networks 25–34 . For example, Bian et al 25 fabricated epoxy resin composites with dopamine modified micro‐BN and KH550 modified nano‐Al 2 O 3 , and found that the composite possessed a TC of 1.182 W·m −1 ·K −1 , when the contents of BN and Al 2 O 3 reached 22.5 and 7.5 wt%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As mechanical strength is an important factor for the practical application of thermal management films, the thermal conductivity and tensile stress of as‐prepared 15P@G‐PVA/G nanocomposite films are compared with previously reported thermal management counterparts at 25 °C. Besides an ultrahigh in‐plane λ of 82.4 W m –1 K –1 , the 15P@G‐PVA/10G nanocomposite film shows a strong tensile strength of 259 MPa (Figure 4f; Table S8, Supporting Information) and the integrated performance is superior to previous work, including BNNS‐, [ 10,17,31,36 ] graphene‐, [ 12,14,33,70 ] and MXene‐based [ 22,32 ] composites. For instance, the BN/NFC nanocomposite paper presents an ultrahigh in‐plane λ of 145.7 W m –1 K –1 but only a weak tensile strength of ≈50 MPa due to high loadings of 50 wt% BN nanosheets, [10] seriously deteriorating the mechanical property of composite paper.…”
Section: Resultsmentioning
confidence: 86%
“…In comparison, lightweight and flexible polymeric composite materials often present a relatively low thermal conductivity due to a strong filler‐polymer interfacial thermal resistance, thus exceedingly restricting their real‐world applications in the 5G device field. [ 11–19 ] Thus, it is urgently desirable to design polymeric thermal management materials with ultrahigh in‐plane thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…It possesses extraordinary high thermal conductivity around 2000–5300 W m −1 K −1 in the in-plane direction at room temperature due to the highly ordered structure and stiff sp 2 -hybridized bondings, as well as excellent electrical and mechanical properties. Lately, coating various substrates with graphene via methods such as chemical vapor deposition, dip coating, spin coating, spray coating, and electrophoretic deposition has been intensively studied by many research groups ( Nooralian et al., 2016 ; Cui et al., 2020 ; Chen et al., 2018 ). Carbon nanotubes are tubular forms of graphene sheets rolled into a cylindrical form with a thermal conductivity around 6600 W m −1 K −1 in the axial direction, which can be produced at various lengths via mostly arc discharge, laser ablation, or chemical vapor deposition ( Gspann et al., 2017 ).…”
Section: Techniques Used For Improving Thermal Conductivitymentioning
confidence: 99%